PIBID AND THE POSSIBILITY OF CONTRIBUTING TO THE TRAINING OF TRANSFORMING - Vidrik, Elisandra Chastel Francischini [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2024)
This text aims to investigate to what extent the Institutional Scholarship Program for Teaching Initiation contributes to the training of future transforming teachers. This is a qualitative research with a case study. The research subjects are undergraduates in Chemistry from a Brazilian federal university and scholarship holders of the Program. As a data collection instrument, we used forms requesting conceptions about education and being a teacher. We asked about the reason for choosing the course and about the satisfaction in taking it. The results indicate that the school is a privileged place for initial training, and although some of them answered that they were not interested in taking a degree in Chemistry, these conceptions were changed during the process. They began to identify with the teaching profession, understanding that in addition to the empathy of teaching and learning at all times, teachers learn to teach, implement changes and be transformative. To acquire this purpose, scholarship holders need training spaces, offering the necessary support to overcome the dichotomy between theory and practice.
Keywords: Initial formation; Institutional Program for Teaching Initiation Scholarships; Theory and practice